EFEKTIVITAS PELAKSANAAN ALOKASI DANA NAGARI (ADN) DI KABUPATEN PASAMAN BARAT - Riza Efendi (STIA Indragiri, 2016)
Abstract : Nagari government as a lowest administrative unit in the province of West Sumatra in driving development in their area should pay attention to all aspects of society and supported by adequate funding to carry out the development. For that reason the Government of West Pasaman give Nagari One Billion Allocation to each Nagari Government in order to facilitate or at least as an incentive for increased community participation in development activities in their area. Therefore, the purpose of this study was to evaluate the effectiveness of Fund Allocation Policy Implementation in West Pasaman Nagari and To Know Obstacles Allocation Policy Implementation Effectiveness Nagari in West Pasaman. This research was conducted in six (6) Nagari administration consisting of three (3) small Nagari administration and three (3) large Nagari administration in West Pasaman. The informant made up of policymakers, the implementor of policies, and policy object. Research carried out by in-depth interviews, observation, documentation studies, and triangulate. The analytical tool used is qualitative data analysis with descriptive approach. The results obtained from the evaluation of the effectiveness of policy Allocation Nagari One Billion Per Nagari in West Pasaman show ( 1 ) Policy Allocation Nagari One Billion Per Nagari ( 1 ) has been able to take a role in reducing poverty and unemployment in Pasaman west , ( 2 ) has been able to improve basic infrastructure in west Pasaman Nagari , and ( 3 ) has been able to increase revenue Nagari. While the obstacles in the Effectiveness of Policy Implementation Fund Allocation Nagari One Billion Per Nagari in West Pasaman are ( 1 ) there are activities that are not related to the alleviation of poverty and unemployment ( 2 ) there are some activities that are of inferior quality , ( 3 ) their aid flows empowerment is not targeted.Keywords : Effectiveness, Nagari government